Mengamalkan Kasih di Tahun Politik 2024: Refleksi Teologis 1 Korintus 13 bagi Pelayanan Hamba Tuhan - Angelista Felmalino Datuan Rongre; Febrianto Pangrelli Gomer; Zhalas Rainhard Mande (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
The political polarity in Indonesia raises the need for values that can unite society. 1 Corinthians 13 offers a perspective of love that can be grounded in politics. This study aims to explore how the values of love in 1 Corinthians 13 can be integrated into political practice to reduce polarization and improve the quality of democracy. Research Methods Using qualitative analysis of the text of 1 Corinthians 13 and related literature studies, this study evaluates the application of love values in the Indonesian political context. The results show that this study confirms that the values of love described in 1 Corinthians 13 have significant relevance in the Indonesian political context, especially ahead of the 2024 elections. An in-depth analysis of this text suggests that love, which includes patience, generosity, and truth, can be the basis for more ethical and constructive political campaigns. The implementation of these values can reduce political tensions, promote constructive dialogue, and create more inclusive and equitable policies, which in turn can improve the quality of public services and build stronger democracies. Thus, the integration of the value of love in political practice can be the key to overcoming polarization and strengthening national unity in Indonesia.